MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V-C SDN MANUKAN KULON II/499 SURABAYA PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN RUANG MENGGUNAKAN MEDIA KONKRIT - Dwi Lestari, Kurnia; Zuhdi, Ulhaq; Wandik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve mathematics learning outcomes in spatial geometry material for class V-C students of SDN Manukan Kulon II/499 Surabaya through the use of concrete media. The subjects of this study were class V-C students of SDN Manukan Kulon II/499 Surabaya consisting of 25 students. The method used in this study was collaborative classroom action (PTKK) which was carried out in two cycles. In cycles I and II, learning was carried out with a focus on the elements of cube and cuboid spatial geometry using concrete media. The results showed an increase in the percentage of learning completion from 52% to 88% in cycle II, with the average learning outcomes of students increasing from 71.2 to 91.2. This shows that the use of improved concrete media and group learning can increase student activity and understanding. It can be concluded that there was an increase in mathematics learning outcomes in spatial geometry material using concrete media for class V-C students of SDN Manukan Kulon II/499 Surabaya.